Significant role and the underly mechanism of cullin-1 in chronic obstructive pulmonary disease - Hao Wenbo; Lin Fei; Kong Weili; Shi Hanbing; Dong Haiying; Guan Zhanjiang; Liu Guohua; Wang Xiao; Wang Li; Liu Moran; Jiang Yunfei (Open Medicine)
This study investigated the role and mechanisms of cullin-1 (CUL1) in chronic obstructive pulmonary disease (COPD).